DEVELOPMENT OF WHEEL DRIVE ELECTRONICS MODEL FOR AUTOMATED MEASUREMENT SYSTEM - Cahyadi, Adrian
Wheel Drive Electronics is a Brushless Direct Current motor control module attached to a reaction wheel. Reaction Wheel is commonly used by spacecraft for three-axis attitude control. The model of Wheel Drive Electronics is made for automatic measuring instrument test materials. The Wheel Drive Electronics model is implemented using a 3 phase half-bridge Integrated Circuits and Arduino microcontroller, with the commutation method used is six-step commutation. The Wheel Drive Electronics test model that is made has some of the basic features of a WDE such as speed control, current control, internal measurement, and communication functions with a Personal Computer. The Wheel Drive Electronics model is tested by giving commands via a Personal Computer and comparing the results of its internal measurements with a measuring instrument. The data compared are in the form of measurement results for velocity, current and temperature. From the result, temperature sensor has resolution of 0,001°C +/- 0,209; current sensor has resolution of 0,01 mA +/- 87,66; speed sensor with average different value of 12 RPM +/- 67; speed control performance withaverage steady state error of 172 RPM +/- 81 and -24 RPM steady state error; 3,544 %OS; and 60 ms settling time on set point of 4000 RPM.